China's 40 Years Demographic Dividend and Labor Supply: The Quantity Myth - Xin Meng (Institute of Labor Economics (IZA), 2023)
In the past forty years the Chinese economy achieved miracle growth and many attributed a significant part of this to China's favourable labour supply flowing from the "demographic dividend": a larger share of working age population (WAPS). Currently, this dividend is slipping away and many in China are very concerned. Against this background I set out to examine the contributions of various dimensions of China's changing WAPS and its impact on economic growth. I show that between 1982-2015 the increase in the WAPS was offset by a decline in the labour force participation rate, resulting in a very limited increase in the quantity of labour supply. I then estimate the association between regional variations in economic growth and changes in factors such as population size, WAPS, migration, education. The results lend little support to the view that increasing WAPS played a major role in China's economic growth over this period.
Keywords: J10; J11; J21; 330; labor supply; demographic dividends; China